2021
DOI: 10.1073/pnas.2108716118
|View full text |Cite
|
Sign up to set email alerts
|

Unnuclear physics: Conformal symmetry in nuclear reactions

Abstract: We investigate a nonrelativistic version of Georgi’s “unparticle physics.” We define the unnucleus as a field in a nonrelativistic conformal field theory. Such a field is characterized by a mass and a conformal dimension. We then consider the formal problem of scatterings to a final state consisting of a particle and an unnucleus and show that the differential cross-section, as a function of the recoil energy received by the particle, has a power-law singularity near the maximal recoil energy, where the power … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…This is consistent with a recent experiment which found that three-body correlations grow slower than two-body ones after an interaction quench [10]. If, instead, three bosons are already resonantly interacting in the two-body sector with s = 4.465 [34] in the initial state before the quench, we expect an anomalous growth law C (3) (t) ∼ t 8.93 reminiscent of unparticle physics [43,44].…”
Section: Borromean System With Three-body Interactionsupporting
confidence: 91%
“…This is consistent with a recent experiment which found that three-body correlations grow slower than two-body ones after an interaction quench [10]. If, instead, three bosons are already resonantly interacting in the two-body sector with s = 4.465 [34] in the initial state before the quench, we expect an anomalous growth law C (3) (t) ∼ t 8.93 reminiscent of unparticle physics [43,44].…”
Section: Borromean System With Three-body Interactionsupporting
confidence: 91%
“…Since then, the effects of unparticles have been explored in many subjects, including collider physics [2][3][4][5][6], neutrino physics [7,8], cosmology and astrophysics [9,10], quantum electrodynamics [11,12], dark energy [13][14][15][16], etc. The recent nonrelativistic extension of unparticle physics has led to a new concept of unnucleus [17] and provided an interpretation of neutral charm mesons near threshold [18].…”
Section: Introductionmentioning
confidence: 99%